Handover analysis of openflow-based mobile networks with distributed control plane. (January 2020) - Panev, Strahil; Latkoski, Pero
Abstract: A centralized controller approach in Software-Defined Networking (SDN) creates problems related to scalability and performance degradation. These problems are the main reason for introducing an architecture of logically distributed controllers. Ensuring the continuity of a user's ongoing session and reducing the interruption time during a handover, is one of the major challenges in today's modern mobile networks. In this paper, we propose a novel analytical approach to model the delay introduced by the handover-related OpenFlow signaling messages in SDN networks using multiple controllers. The analytical model is verified using extensive simulations. The results show that high probability of Packet-in messages causes rapid degradation of network performance. Similarly, by increasing the number of controllers, the number of synchronization messages increases, thus impacting the packet service time. Our findings can facilitate the design of delay-constrained handover approaches in a mobile network with a target system throughput.